2022
DOI: 10.3390/ma15196718
|View full text |Cite
|
Sign up to set email alerts
|

Fe3O4-TiO2 Thin Films in Solar Photocatalytic Processes

Abstract: The optical properties of 5wt% Fe3O4-TiO2 thin films were evaluated in detail with the aim of proposing a mechanism for solar photocatalytic processes and highlighting the advantages over the use of bare TiO2. The results showed that the incorporation of 5wt% Fe3O4 enhanced the optical properties by a redshift to a wavelength in the visible range, reducing the anatase/rutile band gap energy from 3.2 eV to 2.8 eV. Photoluminescence studies reveal a superior separation efficiency of photoexcited electron-hole pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…X for BiVO 4 and Fe 3 O 4 is 6.035 eV and 5.77 eV, respectively. 47,48 E c = 4.5 eV is the scaling factor relating to the normal hydrogen electrode scale (NHE) to the absolute vacuum scale. 49 Using the above equations, the calculated values of the CB and VB for Fe 3 O 4 were found to be 0.56 eV and 1.98 eV, respectively, whereas the values for BiVO 4 were 0.30 eV and 2.77 eV, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…X for BiVO 4 and Fe 3 O 4 is 6.035 eV and 5.77 eV, respectively. 47,48 E c = 4.5 eV is the scaling factor relating to the normal hydrogen electrode scale (NHE) to the absolute vacuum scale. 49 Using the above equations, the calculated values of the CB and VB for Fe 3 O 4 were found to be 0.56 eV and 1.98 eV, respectively, whereas the values for BiVO 4 were 0.30 eV and 2.77 eV, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…93 Some studies reported that the FeO could have an insulating behavior generated by the charge transfer of the 2p state of oxygen to the 3d state of iron. 92 Fe 3 O 4 has a band gap at around 2.85 eV, 94 and has been studied for its potential in photocatalyst and PV applications due to its good optical properties, excellent light absorption, and good optoelectronic properties. 95 Fe 2 O 3 is the highest oxygen state of iron oxides, having a band gap depending on their crystal structures.…”
Section: Distinctive Structures and Properties Of Iron Oxides For Pho...mentioning
confidence: 99%
“…Nishad et al also reported that the core-shell particle size of Fe3O4@ZnO had a lower value of 39 nm, resulting in magnetic materials with luminescence responses [10]. Aguinaco et al performed another type of modification on Fe3O4, where Fe3O4 was composited with titanium oxide (TiO2), resulting in the material applicable as a solar photocatalytic [11]. Fe3O4/TiO2 can also be applied as a photodegradable material.…”
Section: Introductionmentioning
confidence: 99%